2000
DOI: 10.3354/meps197067
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nutrient cycling and related benthic nutrient and oxygen fluxes during a spring phytoplankton bloom in South San Francisco Bay (USA)

Abstract: Benthic oxygen uptake and nutrient releases of N, P and Si were measured weekly at 2 sites in South San Francisco Bay around the 1996 spring bloom. Exchanges across the sediment-water interface were estimated from whole core incubations performed in the laboratory at in situ temperature and in dark. Fluxes changed significantly on a weekly time scale. Over a period of 15 wk the fluxes of dissolved inorganic N, P and Si ranged from -40 to +200, 0 to 13 and from 30 to 400 pm01 m-' h-' respectively. Sediment oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 35 publications
2
50
2
Order By: Relevance
“…This is consistent with reoxygenation of the sediments during winter mixing and lower biological process rates in the colder water. This range of levels is comparable with SOD rates of -0.19 to -0.7 g m -2 day -1 reported in the outer Thames estuary (Trimmer et al 2000), -0.17 to -0.67 g m -2 day -1 in the coastal waters of Denmark (Forster et al 1999), and up to -0.56 g m-2 day -1 before the spring bloom in South San Francisco Bay (Grenz et al 2000).…”
Section: Sediment Flux/regenerationsupporting
confidence: 62%
“…This is consistent with reoxygenation of the sediments during winter mixing and lower biological process rates in the colder water. This range of levels is comparable with SOD rates of -0.19 to -0.7 g m -2 day -1 reported in the outer Thames estuary (Trimmer et al 2000), -0.17 to -0.67 g m -2 day -1 in the coastal waters of Denmark (Forster et al 1999), and up to -0.56 g m-2 day -1 before the spring bloom in South San Francisco Bay (Grenz et al 2000).…”
Section: Sediment Flux/regenerationsupporting
confidence: 62%
“…Previous research has demonstrated that MeHg is produced in San Francisco Bay sediments (Olson and Cooper 1974; Marvin-DiPasquale and Agee 2003), presumably as a result of methylation of inorganic Hg by bacteria that reduce sulfate and/or Fe (Benoit et al 2003;Kerin et al 2006). As the bloom decayed, conditions would have been favorable for mercury methylation because the decomposing algae likely depleted dissolved oxygen in sediments, as was seen following the South Bay bloom in 1996 (Grenz et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…At a species to community level, site-to-site comparisons reveal that benthic macroinvertebrate and diatom species diversity is a function of total dissolved solid concentration, conductivity or salinity in some streams, lakes and fjords (Metzeling, 1993, Ryves et al, 2004. Solute fluxes, especially the amount of Si relative to other potentially limiting nutrients, can be a predictor of phytoplankton blooms and diatom growth (LePape et al, 1996;Grenz et al, 2000). Si concentrations relative to concentrations of Fe, N and P strongly control diatom nutrient uptake and growth rates.…”
Section: Discussionmentioning
confidence: 99%